Accounting Firm Customer Satisfaction Survey - Bagińska, Izabela (Journal of Education, Health and Sport, 2020)
Competition on the market means that the accounting firms that wish to maintain their position on the market, must seek ways to convince their customers that the services they offer are competitive to those offered by their competitors. An accounting firm must convince the company that it will meet all its needs and it will quarantee proper quality. This article aims to identify the factors determining the quality of services provided by accounting firms. The first part of the study contains a review of the literature on service quality and satisfaction as an important factors of its development. The second part contains the results of an anonymous survey conducted among the companies that benefit from accounting outsourcing. The five-level Likert scale was used in the questionnaire. The survey indicated that the respective factors affect the quality and satisfaction of accounting services provided by accounting firms to a different extent.